Testifying to the Truth: Paul Ricœur and Jean-Luc Nancy on the Theological Turn. Issue 2 (July 2019) - Collins, Ashok
Abstract : As one of the most controversial movements in contemporary French thought, the theological turn within phenomenology raises important questions about the limits of philosophical enquiry and its capacity to circumscribe absolutes such as the notion of truth. In this article, I critique Paul Ricœur's hermeneutic phenomenology through the lens provided by Jean-Luc Nancy's deconstruction of Christianity project. Although these two thinkers are usually viewed as differing markedly in their approaches to the turn, in fact there are numerous points of intersection that can be traced between them. I draw them into conversation with each other by exploring their respective hermeneutic readings of the Gospels, arguing in the process that such a dialogue can provide an alternative critical perspective on the boundary between philosophy and theology. I conclude by suggesting that Ricœur and Nancy's shared emphasis on interpretative flexibility necessitates in turn a testimonial moment in which truth can be recognized and acted upon within a community of praxis.